2011
DOI: 10.1017/s0007114511001814
|View full text |Cite
|
Sign up to set email alerts
|

Use of pedometers to measure the relationship of dog walking to body condition score in obese and non-obese dogs

Abstract: The objective of the present study was to utilise an accurate canine pedometer methodology and to assess the relationship between activity and body condition score (BCS) in dogs. Initial methodology validation used videography and pedometer step measurements to assess actual steps taken in comparison with pedometer readings for twenty large, medium and small dogs. During the validation, dogs considered to be medium or large breed showed no significant difference between pedometer readings and actual steps take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 17 publications
5
25
3
Order By: Relevance
“…Previous data suggest an inverse relationship between the number of owner steps (measured by pedometer) and canine BCS (Warren et al 2011). In our study, however, BCS and weight improved in both groups (SC and PA) during Phase II of the study, despite no statistically significant difference in number of walking steps.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Previous data suggest an inverse relationship between the number of owner steps (measured by pedometer) and canine BCS (Warren et al 2011). In our study, however, BCS and weight improved in both groups (SC and PA) during Phase II of the study, despite no statistically significant difference in number of walking steps.…”
Section: Discussioncontrasting
confidence: 69%
“…Interactive exercise between dogs and owners enhances the human-animal bond and represents a cost-effective way to increase canine activity, promote health, and optimize pet weight (LaFlamme and Kuhlman 1995;Tripanny, Funk and Buffington 2003). Recent studies using pedometers to assess the relationship between activity (daily steps) and body condition score in dogs show an inverse relationship (Warren et al 2011).…”
Section: Anthrozoösmentioning
confidence: 99%
“…This finding corresponds to a previous study that demonstrated no change in spontaneous Journal of Small Animal Practice • Vol 60 • July 2019 • © 2019 British Small Animal Veterinary Association activity level in dogs undergoing weight loss (Morrison et al 2014). In contrast, Warren et al (2011) found that a dog's BCS inversely correlated with average daily steps. The range of BCS in our study population was narrow with most dogs having close to ideal BCSs.…”
Section: Discussionsupporting
confidence: 90%
“…Fifty-five dogs with a body condition score [17, 18] between 3–6 out of 9, included German shepherd ( n = 3), Golden Retriever ( n = 12), Labrador Retriever ( n = 18), Beagle ( n = 2), Pug ( n = 5), Shih Tzu ( n = 4), French Bulldog ( n = 2), American Pit Bull Terrier ( n = 5), and Bangkaew ( n = 4). The dog were randomized and categorized into three groups.…”
Section: Methodsmentioning
confidence: 99%